2021
DOI: 10.1097/ju.0000000000001786
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Intravesical Recurrence after Minimally Invasive Nephroureterectomy for Upper Tract Urothelial Cancer (ROBUUST Collaboration)

Abstract: Purpose:Intravesical recurrence (IVR) after radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC) has an incidence of approximately 20%–50%. Studies to date have been composed of mixed treatment cohorts—open, laparoscopic and robotic. The objective of this study is to assess clinicopathological risk factors for intravesical recurrence after RNU for UTUC in a completely minimally invasive cohort.Materials and Methods:We performed a multicenter, retrospective analysis of 485 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
2
36
1
Order By: Relevance
“…Given the large differences in baseline BMI between Asian, and Western populations, collaborative international studies are needed to explained the controversy after rigorous matching. A meta-analysis including 10 studies showed that diabetes increased the risk of IVR in UTUC patients (21), and an international retrospective study discovered that hypertension was a significant risk factor for IVR based on data set from 17 centers worldwide (22). However, the effect of diabetes and hypertension on overall or cancer-specific survival has not been proven.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large differences in baseline BMI between Asian, and Western populations, collaborative international studies are needed to explained the controversy after rigorous matching. A meta-analysis including 10 studies showed that diabetes increased the risk of IVR in UTUC patients (21), and an international retrospective study discovered that hypertension was a significant risk factor for IVR based on data set from 17 centers worldwide (22). However, the effect of diabetes and hypertension on overall or cancer-specific survival has not been proven.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the schedule or regime of adjuvant chemotherapy which has a potential impact on survival outcomes was not reported in the data repository. Third, the surgical method, such as open or laparoscopic, and the approach for bladder cuff management were not included in the SEER, and these factors may affect RLN yields or survival outcomes ( 24 ). Fourth, no data about smoking status or renal function before or after the operation were offered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Katims et al (31) reported the risk factors for IVR after minimally invasive RNUx. They reported that IVR occurred in 22.7% of patients who underwent RNUx.…”
Section: Discussionmentioning
confidence: 99%